REPRESENTASI MULTIKULTURALISME DALAM SEPAK BOLA PRANCIS MASA KINI - Fadli Muhammad Athalarik; Arif Susanto (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
The arrival of a large number of immigrants made France feel such a huge impact, one of which is the presence of a multicultural situation in French society. One portrait of multiculturalism that deserves the spotlight is football. This study aims to determine the cultural diversity in French society and how multiculturalism is represented in French football. The research method in this research is descriptive qualitative. To analyze this phenomenon, researchers used the Concept of Multicultural and Cross-Cultural Communication. The results of this study stated that in the field of football, multiculturalism can be said to be a gift, because with the presence of many immigrants, France won a lot of glory on the European and World soccer stage. However, on the other hand, the arrival of Multiculturalism in France, faced many challenges and problems in it. The impact caused by multiculturalism is not a small impact, from the existence of crime and terrorism, to the problems present in society such as Islamophobia, xenophobia, anti-semitism and so forth.